Ethylene conversion to higher hydrocarbon over copper loaded BZSM-5 in the presence of oxygen - Mat, Ramli; Amin, Nor Aishah Saidina; Ramli, Zainab; Abu Bakar, W. Azelee W. (Kexue Chubaneshe/Science Press, 2006)
The successful production of higher hydrocarbons from methane depends on the stability or the oxidation rate of the intermediate products. The performances of the BZSM-5 and the modified BZSM-5 catalysts were tested for ethylene conversion into higher hydrocarbons. The catalytic experiments were carried out in a fixed-bed micro reactor at atmospheric pressure. The catalysts were characterized using XRD, NH3-TPD, and IR for their structure and acidity. The result suggests that BZSM-5 is a weak acid. The introduction of copper into BZSM-5 improved the acidity of BZSM-5. The conversion of ethylene toward higher hydrocarbons is dependent on the acidity of the catalyst. Only weaker acid site is required to convert ethylene to higher hydrocarbons. The loading of Cu on BZSM-5 improved the selectivity for higher hydrocarbons especially at low percentage. The reactivity of ethylene is dependent on the amount of acidity as well as the presence of metal on the catalyst surface. Cu1%BZSM-5 is capable of converting ethylene to higher hydrocarbons. The balances between the metal and acid sites influence the performance of ethylene conversion and higher hydrocarbon selectivity. Higher loading of Cu leads to the formation of COx.